BUDAYA KOMUNIKASI ORGANISASI LPP RRI DENPASAR DALAM SOSIALISASI APLIKASI MOBILE RRI DIGITAL - Sari, Ida Ayu Putu Widya Indah; I Nyoman Yoga Segara; I Nyoman Ananda (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2025)
RRI Digital, a mobile application based on radio streaming technology owned by LPP RRI, facilitates public access to information and entertainment. To build employee understanding of RRI Digital, the Denpasar branch of LPP RRI initiated internal organizational communication. During the organizational communication process in the field, it was found that the delivery of memorandums occurred through one-way communication via WhatsApp groups. Initial observations revealed various interpretations of memorandums and instructions, resulting in differences in attitudes and knowledge among employees. The research questions of this study are (1) understanding the communication process, (2) communication barriers, and (3) analyzing the impact of socializing the RRI Digital mobile application on employees. Based on the analysis of Organizational Control Theory, bureaucratic and technical control were the dominant communication cultures during the socialization process of the RRI Digital application. However, concertive control has not been fully implemented by unit leaders. Challenges faced by the RRI Denpasar organization during socialization included the dominance of personal communication networks and greater exposure to third-party information within large group communication networks. The impact of organizational communication on the socialization of the RRI Digital application showed similarities in a positive and optimistic speaking culture. Differences in communication were seen due to communication gaps between leadership and staff, despite information being shared on platforms commonly used by both communicators and recipients.